Category of modality from the point of view of logic and linguistics: similarities, differences and prospects for synthesis - Kastsiuchenka, Viktoryia Y. (Journal of the Belarusian State University. Philology, 2019)
Modal categories in logic and linguistics are comparable. Two aspects of the category of modality are correlated in such a way that a certain composition of language means (grammatical and lexical) corresponds to the categories developed in logic (meanings of modal logic). Thus, the five major categories of modal logic (cognitive modality, deontic modality, axiological modality, teleological and metalanguage modality) which correlate with the systematization of linguistic categories of modal meanings proposed in the article, differ in their lexical manifestation, namely, teleological modality is represented in two forms: modally marked speech acts; illocutionary verbs, which define speech acts. Cognitive modalities are divided into two subgroups: epistemic modality, which is expressed by predicates with the meaning of thinking, knowledge, assumption and alethic modality that is expressed by parenthetical words and phrases with the meaning of confidence, assumption, doubt. Deontic modality is represented by words with the semantics ‘can’, ‘can not’, ‘must’, ‘allowed’, ‘prohibited’. The axiological modality is expressed by: evaluative adjectives and adverbs; parenthetical words and phrases; verbs and predicates expressing emotions and feelings based on positive or negative evaluation of the object. Metalanguage modality is expressed by a special class of parenthetical words and phrases, as well as verbs of commenting. The proposed approach allows to systematize contradictory and in various degree detailed classifications of modal meanings from a wider position, contributes to the development of a certain system of modality.